2020
DOI: 10.5539/ijms.v12n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Key Success Factors of Social Marketing in Promoting Environmental Consciousness: A Dematel-Based Approach

Abstract: Due to the overuse of the environment and natural resources, our environment has suffered long-term damage and natural disasters have been exacerbated by climate change, resulting in a significant impact on people’s livelihood and security. People must consider saving the environment as everyone’s responsibility. Hence, Environmental consciousness should be promoted to inspire public participation. This study used the Decision Making Trial and Evaluation Laboratory (DEMATEL) method to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The most significant aspect of DEMATEL is the function of constructing the relation and structure of the criteria in multi-factors decision making area [ 48 , 49 , 50 ]. In addition, the DEMATEL method was successfully applied in many situations, such as marketing strategy, social marketing, environmental issues, information systems, service quality and in the business ecosystem [ 51 , 52 , 53 , 54 ]. However, the problem of the organization is mostly under uncertain circumstances.…”
Section: Methodsmentioning
confidence: 99%
“…The most significant aspect of DEMATEL is the function of constructing the relation and structure of the criteria in multi-factors decision making area [ 48 , 49 , 50 ]. In addition, the DEMATEL method was successfully applied in many situations, such as marketing strategy, social marketing, environmental issues, information systems, service quality and in the business ecosystem [ 51 , 52 , 53 , 54 ]. However, the problem of the organization is mostly under uncertain circumstances.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that constructing effective messages to target audiences was the most important success factor, followed by meeting the need for beneficiaries to enact voluntary behavior change. Importantly, the author warned that success was determined by having enough resources/ continued funding to carry out the social marketing intervention (Liao, 2020b), signifying funders' role, power and authority in measuring success (Akbar et al, 2021b).…”
Section: Literature Review Interpretation Of Successmentioning
confidence: 99%
“…Others do not precisely define success but associate the term with compliance with certain conditions that predict success. Several terminologies are interchangeably used to present these conditions in the literature, including frameworks (Cohen and Andrade, 2018; NSMC, 2010), factors (Akbar et al , 2021a), foundations (Kim et al , 2021), criteria (Andreasen, 2002; Lynes et al , 2014; Liao, 2020b) or principles (Lee, 2020; Carins, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations